Factors for Selection of Medical Records and Health Information Study Programs for New Students at Universitas Esa Unggul, Jakarta, Indonesia - Dewi, Sisilia Kartika; Nanda Aula Rumana; Dina Sonia; Lily Widjaja (Arkus, 2024)
University is one of the educational facilities in order to equip oneself with the knowledge and skills needed to face the future. There are several factors that underlie prospective students in determining the major they want to enter at university. This study aimed to describe the factors for selecting a medical records and health information study program for new students at Universitas Esa Unggul, Jakarta, Indonesia. This research is a descriptive observational study. The inclusion criteria for this research were new students from the Universitas Esa Unggul medical records program class of 2023 who were willing to take part in this research process. The research subjects were carried out using proportional random sampling techniques. A total of 129 students participated in this research. Data collection was carried out using a questionnaire. The study results showed that most of the students were teenagers (58.1%) and women (67.4%) and chose the regular program (76.7%). The highest factors influencing new students' decisions are accreditation (university image) (90.31%) and employment availability (89.73%), while the lowest is the interest factor, namely the dream of becoming a medical recorder (76.16%). In conclusion, the study program image factor (accreditation) is the underlying factor in selecting a medical records and health information study program for new students at Universitas Esa Unggul, Jakarta, Indonesia.